PEMANFAATAN ANALYTICAL HIERARCHY PROCESS (AHP) PADA E-VOTING PEMILIHAN KETUA OSIS - Tri Astuti; Galuh Kusumastuti; Rudi Fitriyanto (Universitas Bumigora, 2017)
The selection of the head of the intra-school student organization (OSIS) is an annual event that is regularly conducted once a year in schools. Todays the election process applied in schools based on the acquisition of the most votes or called conventional voting. The selection is done using the ballots distributed to the students. Problems that occur in conventional voting are quite a lot of invalid ballots, students do not choose, the cost required is high enough and has a pattern of increased costs each year. In addition, in determining the elected candidates when found the same number of votes often confusion and re-election and result in scattering costs for the selection process. Today's increasingly sophisticated technological developments can be used to overcome problems in the conventional voting process by applying e-voting that has a number of advantages. The purpose of this research is to develop e-voting application in choosing the chairman of OSIS as an alternative way of choosing the chairman of OSIS based on decision-making method of Analytical Hierarchy Process (AHP. The system development method used is extreme programming (XP). The result of this research is the e-voting application of OSIS chairman election.